Identifying the influence of solvothermal processing on the structural and electrochemical properties of graphene-like materials for supercapacitor applications - Widanarto, Wahyu; Setiawan, Dedi; Effendi, Mukhtar; Cahyanto, Wahyu Tri; Supriyanti, Retno; Aliim, Muhammad Syaiful; Rahmawati, Dina; Kurniawan, Candra (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is a graphene-like material synthesized from coconut shell biomass via a solvothermal process using ethylene glycol (98%) as the dispersing medium. Were examined are exfoliated carbon nanosheets intended for use as electrode materials in supercapacitors. The research addresses the problem of improving biomass-derived carbon materials’ structural quality and electrochemical performance for energy storage. The solvothermal process was applied at varying ethylene glycol concentrations (1, 3, and 5 mg/ml), and the synthesized samples were compared with an untreated control. The results show that the sample treated with 3 mg/ml (SL-2) exhibited the most favorable characteristics, including reduced interlayer spacing (0.39 nm), formation of thin nanosheets, and decreased oxygen-containing functional groups, as evidenced by TEM, FTIR, and EDS analyses. These structural improvements are attributed to the combined effects of thermal energy and solvent-assisted exfoliation, which facilitated partial deoxygenation and reordering of carbon layers. BET analysis revealed a high specific surface area of 872.886 m2/g, contributing to enhanced ion accessibility. Electrochemical measurements demonstrated a specific capacitance of 31.50 F/g for SL-2, significantly higher than the untreated sample (6.32 F/g), along with lower internal resistance (1.87 Ω) and prolonged charge-discharge time (39.90 s), indicating improved ion transport and conductivity. These results highlight the potential of this sustainable and tunable method for producing cost-effective, eco-friendly supercapacitor electrodes